228 Standardized Ileal Digestibility of Partially Defatted Black Soldier Fly Larvae Meal in Growing Pig Diets. (8th October 2021) - Tansil, Fiona; Huber, Lee-Anne; Kiarie, Elijah; Columbus, Daniel A; Shoveller, Anna-Kate
Abstract: New ingredients need to be characterized both chemically and in vivo, then compared to commonly-used protein ingredients before they can be considered for use in feeds. The objective of the present study was to determine the standardized ileal digestibility (SID, %) of amino acids (AA) of partially defatted black soldier fly larvae meal (BSFLM) (49.7% CP; 14.4% crude fat as fed). Subsequently, these results were compared to the SID AA of common protein ingredients in swine feed, fish meal (FM) and soybean meal (SBM) (NRC 2012), and to published full-fat (FF) BSFLM SID values. Six ileal-cannulated barrows (18.03 ± 0.67 kg BW) were used in a 2x2 Latin square design and fed either a nitrogen-free diet (NFD) or BSFLM-containing diet over two 11-d experimental periods. In each period, barrows were adapted for 7 days to the diet and ileal digesta collection was conducted on day 10 and 11 for 8h per day. Basal endogenous AA losses (EAAL) were calculated from pigs fed the NFD and as expected, the ileal AA content were significantly higher for pigs fed the BSFLM diet than NFD (P < 0.05). SID for AA were then calculated based on the obtained EAAL values following Stein et al., 2007. For essential AA, the SID of BSFLM were all above 82%, the highest being Arg (93.76%), followed by Met (91.32%), and Phe (89.80%). The SID of essential AA were on average 5.0% higher in BSFLM than FM, but 2.7% lower than SBM. When compared to the FF BSFLM, SID of essential AA of BSFLM were 1–5% higher, except for Phe and Thr. These results suggest that partially defatted BSFLM is a promising alternative protein ingredient in growing pig diets, which has a more digestible AA profile than FM, only slightly lower than SBM, and comparable to the FF BSFLM.